2020
DOI: 10.5194/ms-11-39-2020
|View full text |Cite
|
Sign up to set email alerts
|

Boundary-layer separation in circular diffuser flows in the presence of an external non-uniform magnetic field

Abstract: Abstract. The focus of the present work is on the investigation of the separation point and its relative location in a circular diffuser carrying incompressible laminar flow in the presence of a non-uniform external magnetic field. Two different approaches are deployed in the present analysis. In the first approach, a similarity transform is applied to reduce the momentum equation to the nonlinear ordinary differential equation (ODE). The ODE is solved by a dual integral–numerical method and the separation pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, when Deborah number increases, the velocity is also increased. The effect of non-uniform magnetic intensity on separation in a diffuser with Newtonian fluid flow is provided by Moghimi et al [13]. The results indicated that by increasing the magnetic field intensity, the Lorentz force increased; then, the separation point was delayed .…”
Section: Introductionmentioning
confidence: 98%
“…However, when Deborah number increases, the velocity is also increased. The effect of non-uniform magnetic intensity on separation in a diffuser with Newtonian fluid flow is provided by Moghimi et al [13]. The results indicated that by increasing the magnetic field intensity, the Lorentz force increased; then, the separation point was delayed .…”
Section: Introductionmentioning
confidence: 98%
“…MHD Maxwell fluid model flow with the characteristic of Falkner-Skan was investigated by Abbasbandy et al [15] and results were computed both analytically and numerically. Other related research of MHD can also be found in [16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…27,28 Furthermore, the authors provided semi-analytical studies to analyze the non-uniform magnetic field effect on the separation point for both Newtonian and non-Newtonian fluid flow in a diffusor. 29,30 According to the above literature, identification and control of the separation phenomena in 2Ddivergent MHD channel flows under the influence of a constant applied magnetic field has been presented; however, investigation of the separation point with considering variable magnetic field intensity has not been studied numerically. Therefore, in the present study, we aim to extend the authors' previous work; therefore, the research's main objective is to determine the separation point under a nonuniform magnetic field, which is more realistic in engineering applications.…”
Section: Introductionmentioning
confidence: 99%